TRAINING OF DEFECTORS FOR THE HEALTH CARE SYSTEM: PROBLEMS AND PROSPECTS - G. Kozlovskaya; N. Mayatskaya; A. Hodzhayan (Вестник Северо-Кавказского федерального университета)
The article discusses the historical aspects ofthe formation ofthe system oftraining ofdefectologists, the role of biomedical competencesfor solving their professional tasks; highlights the trends ofmodernization of the higher defectological education system and the experience of designing educational programs for the training ofpathologists for the health care system It also presents the experience of training specialists in the field of clinical speech therapy and the development prospects of the specialty.